Knowledge and perceptions of organ donation: a cross-sectional study among urban residents of Vijayapura, Karnataka - K., Jafeya Rekanaah; Yadavannavar, M. C.; Pattankar, Tanuja P.; Rangoli, A. M. (International Journal Of Community Medicine And Public Health, 2025)
Background: Organ donation saves lives but India faces a major gap between demand and availability of donor organs. Contributing factors include low awareness, myths, cultural and religious beliefs, and limited legal knowledge. Understanding community perceptions is vital for effective health education and policy strategies to improve organ donation. This study aimed to assess the knowledge, attitudes and practices related to organ donation among urban residents of Vijayapura, Karnataka and to identify the socio-demographic factors influencing these perceptions. Methods: A two-month cross-sectional study in an urban field practice area of North Karnataka included 299 randomly selected participants. Data were collected via a house-to-house survey using a semi-structured questionnaire on socio-demographics and organ donation. Analysis with SPSS v20 used Chi-square tests, considering p<0.05 statistically significant. Results: Among 299 participants, awareness of organ donation was 72.2%, with eyes being the most recognized organ. Nearly half knew donation is possible from both living and deceased, but 65.2% were unaware of legal aspects. Though religion was not a major barrier, actual commitment was low, with only 34.8% willing to pledge and 10% registered. Knowledge was significantly associated with education and socio-economic status. Conclusions: The study showed moderate awareness of organ donation among North Karnataka residents but highlighted gaps in legal knowledge and commitment. Education and economic status influenced attitudes. Targeted awareness campaigns, community engagement, and educational interventions are essential to dispel myths, encourage pledging, and reduce the demand-supply gap.